A Novel Mutation in an NPXY Motif of β Integrin Reveals Phenotypes Similar to him-4/hemicentin - Qiu, Zhongqiang; Sheesley, Peter; Ahn, Jeong H.; Yu, Eun-Jeong; Lee, Myeongwoo (Frontiers in Cell and Developmental Biology, 2019)
Integrin, an αβ heterodimeric cell surface receptor for the extracellular matrix (ECM), carries two tyrosine phosphorylation motifs in the cytoplasmic tail of the β subunit. NPXY (Asn-Pro-x-Tyr) is a conserved tyrosine phosphorylation motif that binds to the phospho-tyrosine binding (PTB) domain. We generated a tyrosine to glutamic acid (E) mutation to modify tyrosine (Y) into a negatively charged amino NPXY in the βpat-3 integrin of Caenorhabditis elegans. The transgenic rescue animal displayed defects in gonad migration and tail morphology. Also, the mutant animals produced a high number of males, suggesting that the Y to E mutation in βpat-3 integrin causes a phenotype similar to that of Him mutant. Further analyses revealed that males of pat-3(Y804E) and him-4/hemicentin share additional phenotypes such as abnormal gonad and unsuccessful mating. A pat-3 transgenic rescue mutant with a non-polar phenylalanine (F) in NPXY, pat-3(Y792/804F), suppressed the high male number, defective mating, inviable zygote, and the abnormal gonad of him-4 mutants, indicating that Y to F mutation in both NPXY motifs suppressed the him-4 phenotypes. This finding supports the idea that the ECM determines the activation state in integrin NPXY motifs; him-4/hemicentin may directly or indirectly interact with integrins and maintain the NPXY non-charged. Our findings provide new insight into a suppressive role of an ECM molecule in integrin NPXY activation.